2014
DOI: 10.1371/journal.pone.0095976
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Profile and Pulsed–Field Gel Electrophoresis Analysis of Salmonella enterica Isolates from Humans in Turkey

Abstract: This study was conducted for typing Salmonella enterica subspecies enterica strains in Turkey using pulsed–field gel electrophoresis (PFGE) and plasmid DNA profile analysis. Fourty-two strains were isolated from clinical samples obtained from unrelated patients with acute diarrhea. The samples were collected from state hospitals and public health laboratories located at seven provinces in different regions of Turkey at different times between 2004 and 2010. The strains were determined to belong to 4 different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
4
25
0
4
Order By: Relevance
“…were completely resistant to nalidixic acid and gentamycin during the 2012 and 2013 outbreaks in Iran; these findings are consistent with the data from other studies in Iran and neighboring countries (24)(25)(26). A study by Ashtiani et al (27) out of Iran showed that the resistance rate to nalidixic acid was 42.3%.…”
Section: Discussionsupporting
confidence: 89%
“…were completely resistant to nalidixic acid and gentamycin during the 2012 and 2013 outbreaks in Iran; these findings are consistent with the data from other studies in Iran and neighboring countries (24)(25)(26). A study by Ashtiani et al (27) out of Iran showed that the resistance rate to nalidixic acid was 42.3%.…”
Section: Discussionsupporting
confidence: 89%
“…PFGE produces comparable data of genotypic characteristics of Salmonella strains and it is accepted as the gold standard among molecular methods [12,13]. In addition to this, it has been used in typing Salmonella in human patients, animal sources and foods because of its discriminatory power and high reproducibility [14][15][16]. Numerous reports have been documented that using the highly discriminatory technique of PFGE was successful to track the source of Salmonella infections in different serovars [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Maraki and Papadakis 4 determined S. Enteritidis as the most commonly isolated serotype of Salmonella (37.3%). In another study by Ozdemir and Acar, 16 S. Enteritidis was determined as the most commonly isolated serotype from Salmonella isolates collected from 4 different provinces of Turkey. Our results show consistency with the literature.…”
Section: Discussionmentioning
confidence: 99%